2010
DOI: 10.14430/arctic387
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ancient Feather Fragments Found in Melting Alpine Ice Patches in Southern Yukon

Abstract: ABSTRACT. Twelve ancient artifacts or fragmented feather samples recovered from melting alpine ice patches in southern Yukon were analyzed in order to identify the species of birds associated with the ice patches or used on weapons recovered from these sites. The identification of bird species used by ancient hunters as long ago as 4500 BP enhances our insight into the customs, culture, and sophistication of life at that time. Downy feather barbs were found on two samples and microscopically identified as duck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
(8 reference statements)
1
18
0
2
Order By: Relevance
“…In many parts of the world, recent glacier recession has opened an entirely new window on the palaeoecology, vegetation history, and archaeology of sites at high elevations (Dyurgerov and Meier, 2000;Farnell et al, 2004;Dove et al, 2005;Nesje, 2009;Menounos et al, 2009;Nesje et al, 2011;Andrews and MacKay, 2012;Callanan, 2012). In forefields of mountain glaciers and perennial snow and ice patches, in most cases quite close to the tree line, exposure of megafossil tree remnants of different species spanning major parts of the Holocene is quite common (e.g., Nicolussi and Patzelt, 2000;Hormes et al, 2001;Schlüchter and Jörin, 2004;Koch et al, 2007;Benedict et al, 2008;Joerin et al, 2008;Wiles et al, 2008;Scapozza et al, 2010;Koehler and Smith, 2011;Nicolussi and Schlüchter, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, recent glacier recession has opened an entirely new window on the palaeoecology, vegetation history, and archaeology of sites at high elevations (Dyurgerov and Meier, 2000;Farnell et al, 2004;Dove et al, 2005;Nesje, 2009;Menounos et al, 2009;Nesje et al, 2011;Andrews and MacKay, 2012;Callanan, 2012). In forefields of mountain glaciers and perennial snow and ice patches, in most cases quite close to the tree line, exposure of megafossil tree remnants of different species spanning major parts of the Holocene is quite common (e.g., Nicolussi and Patzelt, 2000;Hormes et al, 2001;Schlüchter and Jörin, 2004;Koch et al, 2007;Benedict et al, 2008;Joerin et al, 2008;Wiles et al, 2008;Scapozza et al, 2010;Koehler and Smith, 2011;Nicolussi and Schlüchter, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…; Dove et al . ). Studies have claimed to have found evidence of intact keratin based on immunohistochemistry experiments (Schweitzer et al .…”
mentioning
confidence: 97%
“…They provide evidence of continuity of technical knowledge over at least 300 years of Athapaskan traditions. The feathers, however, could not be identified (Dove et al, 2005).…”
Section: Fletching Of the Proximal Endmentioning
confidence: 90%
“…The split feathers of the 440 radiocarbon-yearold arrow shaft JbVa-1:1 (Fig. 2g) were identified as eagle feathers (Dove et al, 2005), indicating the antiquity of technological traditions transmitted orally and reported on by early ethnographers and present-day oral history.…”
Section: Fletching Of the Proximal Endmentioning
confidence: 99%
See 1 more Smart Citation